Impairment of coronary flow velocity reserve and global longitudinal strain in women with cardiac syndrome X and slow coronary flow. Issue 1 (July 2020) - Jovanovic, Ivana; Tesic, Milorad; Giga, Vojislav; Dobric, Milan; Boskovic, Nikola; Vratonjic, Jelena; Orlic, Dejan; Gudelj, Ognjen; Tomasevic, Miloje; Dikic, Miodrag; Nedeljkovic, Ivana; Trifunovic, Danijela; et al.
Highlights: Cardiac syndrome X (CSX) patients have impaired coronary flow velocity reserve (CFVR). Left ventricular global longitudinal strain (LVGLS) values are reduced at rest and during exercise in CSX patients. CFVR and LVGLS are more profoundly impaired in CSX subgroup with slow coronary flow (SCF). Presence of SCF in CSX patients also reflects worse clinical presentation. Findings might contribute to further risk stratification of this population. Abstract: Background: Microvascular dysfunction (MVD) is associated with adverse prognosis and may account for abnormal stress tests and angina symptoms in women with cardiac syndrome X (CSX). The aim of our study was to assess MVD by coronary flow velocity reserve (CFVR) and left ventricular (LV) contractile function by LV global longitudinal strain (LVGLS) in CSX patients with respect to presence of slow coronary flow (SCF). It was of additional importance to evaluate clinical status of CSX patients using Seattle Angina Questionnaire. Methods and results: Study population included 70 women with CSX (mean age 61 ± 7 years) and 34 age-matched controls. CSX group was stratified into two subgroups depending on SCF presence: CSX-Thrombolysis In Myocardial Infarction (TIMI) 3- normal flow subgroup (n = 38) and CSX-TIMI 2- SCF subgroup (n = 32) as defined by coronary angiography. LVGLS measurements and CFVR of left anterior descending (LAD) and posterior descending (PD) artery were performed. CFVR-LAD and PD were markedly impaired in CSX group compared to controls (2.34 ± 0.25 vs 3.05 ± 0.21, p  < 0.001; 2.32 ± 0.24 vs 3.01 ± 0.13, p  < 0.001), and furthermore decreased in CSX-TIMI 2 patients. Resting, peak, and ΔLVGLS were all significantly impaired in CSX group compared to controls (for all p  < 0.001), and furthermore reduced in CSX-TIMI 2 subgroup. Strongest correlation was found between peak LVGLS and CFVR LAD (r = −0.784, p  < 0.001) and PD (r = −0.772, p  < 0.001). CSX-TIMI 2 subgroup had more frequent angina symptoms and more impaired quality of life. Conclusions: MVD in CSX patients is demonstrated by reduction in CFVR and LVGLS values. SCF implies more profound impairment of microvascular and LV systolic function along with worse clinical presentation.